Sound the jubilee - Forrester, Sandra (New York : Lodestar Books, 1995)
A slave and her family escape from their North Carolina plantation during the early part of the Civil War, finding refuge on Roanoke Island.
Wilson's Children
Wilson's Junior High School
Elem. School Library Collection
6.0
5-8
Keywords: Slavery -- Fiction; Slavery -- Fiction; United States -- History -- Civil War, 1861-1865 -- Juvenile fiction; Roanoke Island (N.C.) -- History -- Fiction; United States -- History -- Civil War, 1861-1865 -- Fiction; Roanoke Island (N.C.) -- History -- Fiction; United States -- History -- 1861-1865, Civil War -- Fiction